Evaluating the impacts of watershed rehabilitation and irrigation interventions on vegetation greenness and soil erosion using remote sensing and biophysical modelling in Feresmay watershed in Ethiopia - Bayissa, Yared; Dile, Yihun T.; Srinivasan, Raghavan; Ringler, Claudia; Lefore, Nicole; Worqlul, A. W. (Informa UK Limited, 2023)
Soil erosion and subsequent land degradation undermine efforts to ensure food security and environmental sustainability in Ethiopia. The government of Ethiopia has implemented extensive soil and water conservation (SWC) programs in severely degraded and food-insecure areas of the country, in some cases integrated with subsequent or parallel irrigation development. However, the effectiveness of these interventions has not been extensively evaluated. This study, therefore, evaluates the performance and impacts of SWC practices in terms of improving vegetation greenness and reducing soil erosion in Feresmay watershed in Ethiopia. Long-term Landsat-based Normalised Difference Vegetation Index (NDVI), Revised Universal Soil Loss Equation (RUSLE), and Soil and Water Assessment Tool (SWAT) were used for change-detection analysis before and after the implementation of various SWC interventions. The results revealed the positive impacts of SWC interventions in improving the vegetation greenness and soil erosion reduction although the outcome varied by intervention. Increased vegetation greenness was observed largely in areas where area closure with catchment treatment (ACCT) and impacts of irrigation (IRR) interventions are dominant, while relatively little impact was observed at the watershed level analysis. Although these interventions helped to reduce soil loss, the results highlighted the need for more SWC interventions to minimise further soil loss.